Comparison of Molecular Testing Methods in Detecting Drug Resistance Tuberculosis - Yanika, Grevy; Alamanda, Cut Nur Cinthia; Rachman, Rifky Waluyajati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Tuberculosis (TB) is the leading cause of infectious disease-related deaths in Indonesia, and the COVID-19 pandemic has led to a decline in TB reporting and an increase in Drug-Resistant Tuberculosis (DR-TB). While traditional culture and Drug Susceptibility Testing (DST) takes 2-8 weeks, therefore, genotypic assays such as GeneXpert, Line Probe Assay (LPA), and sequencing offer faster and more precise diagnosis and drug resistance information.